178 Circulating Micrornas for Predicting and Monitoring Response to Mechanical Circulatory Support from a left Ventricular Assist Device. (31st May 2014) - Morley-Smith, Andrew; Mills, Adam; Jacobs, Steven; Meyns, Bart; Rega, Filip; Simon, Andre; Pepper, John; Lyon, Alexander; Thum, Thomas
Abstract : Purpose: There are few non-invasive techniques to predict and monitor patients' responses to left ventricular assist device (LVAD) therapy. MicroRNAs (miRs) are small noncoding RNAs with intricate roles in cardiovascular disease. They remain stable in the circulation, are readily quantified, and may be useful as new biomarkers. This study sought to identify candidate miR biomarkers for further investigation and to investigate whether these circulating miRs were of myocardial origin. Methods and Results: We studied 55 serial plasma and myocardial samples from 19 patients who underwent HeartMate II LVAD implantation, and used a screening microarray to analyse the change in expression of 1, 113 miRs from pre-implant and 6 months follow-up. Twelve miRs showed significant variation and underwent validation, with miR-1202 and miR-483–3p selected for further study. The key findings in the test cohort (n = 8) were: (1) miR-483–3p showed upregulation after 6 months of LVAD therapy in circulating plasma (median fold change 2.32 (1.30–2.44); p = 0.021) and in ventricular myocardium (median fold change 1.799 (0.717–4.719; p = 0.169). This mirrored the reduction in NT-proBNP levels at 6 months (fold change 0.30 (0.08–0.43); p = 0.004; see Figure ). (2) Using change in NT-proBNP at 3 months as a marker of clinical response to LVAD therapy, baseline expression of plasma miR-1202 identified good versus poor LVAD responders (absolute expression 1.296 (1.293–1.306) vs. 1.311 (1.310–1.318) A.U.; p = 0.004). (3) Both miR-483–3p and miR-1202 are also enriched in ventricular myocardium suggesting the heart as the possible source of these plasma miRs. Conclusions: This is the first report of circulating miR biomarkers in LVAD patients. We demonstrate the feasibility of this approach, and report the potential for miR-483–3p and miR-1202 respectively to monitor and predict response to LVAD therapy. We suggest that changes in miR-483–3p expression could provide a more specific assessment of ventricular function that complements the changes in systemic neuroendocrine milieu recorded by serial measurement of natriuretic peptides, and suggest that miR-1202 could be valuable for judging the likelihood of good response to LVAD support. However, these conclusions are weakened by small sample size and retrospective analysis. We propose further work to study these hypotheses further and elucidate roles for miR-483–3p and miR-1202 in clinical practice and in underlying biological processes.